The analogue of the Mahler—Sprindžuk's theorem for some polynomials in (x, y) of third degree. I - Sliesoraitienė, R. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Р. Слесорайтене. Аналог теоремы Малера—Спринджука для некоторых полиномов третьей степени от двух переменных. IR. Sliesoratienė. Malerio—Sprindžuko teoremos analogas kai kuriems trečio laipsnio dviejų kintamųjų polinomams. I